Los proyectos de vivienda con fines sociales en la ciudad de Guayaquil, su incidencia en el déficit habitacional. - Gonzabay Suárez, Rosa Cristina (2015)
The first chapter reflects the information from which will develop this project which is in the city of Guayaquil, with a population of 2, year 2010 ' 291.158, of which 79% of the sample of the population does not have a homeownership. Most of the population in the city of Guayaquil is floating, i.e. citizens migrating from the field to the city, creating a housing shortage in the aforementioned city………